“I Don’t Hate All Women, Just Those Stuck-Up Bitches”: How Incels and Mainstream Pornography Speak the Same Extreme Language of Misogyny - Tranchese, Alessia (Violence against women, 2021)
This article seeks to establish the connection—via shared discourse—between Incels and mainstream pornography. With an interdisciplinary approach which involves a Corpus Linguistics analysis of Reddit forum data, research into digital behaviors, and a feminist critique, this article focuses on the commonalities between the language of pornography and that of Incels. In doing so, it demonstrates how both pornography and Incels are different manifestations of the same misogyny. The findings of this study highlight the normalization of violence against women (VAW), which continues to be endemic in society, enabled and exacerbated by contemporary technologies.